Improving clinical trial design for hepatocellular carcinoma treatments - Robert G. Gish; Garrett Hisatake (Frontiers Media S.A., 2011)
Despite its place as the third leading cause of cancer deaths worldwide, there are currently no approved chemotherapeutic agents, devices or techniques to treat hepatocellular carcinoma. Importantly, there have been no phase III studies demonstrating survival benefit, nor any randomized studies of treatment except for transarterial chemoembolization and most recently sorafenib. The importance of well-designed clinical trials of agents to treat HCC has never been greater. However, general clinical study design issues, combined with HCC-specific issues pose significant challenges in structuring such studies. HCC-related challenges include the heterogeneity of this cancer and the fact that it is frequently accompanied by significant comorbidities at diagnosis, such as active hepatitis B or C virus replication, substantial past or on-going alcohol use, and cirrhosis, itself often a fatal disease. The recently published comparison of a newer treatment, nolatrexed to doxorubicin, and comments about this study's initial HCC diagnostic criteria, staging system, comparator therapy and choice of endpoints have provided a platform to discuss the challenges unique to the design of HCC clinical trials. The difficulty in accurately framing study results obtained from the constantly changing HCC clinical landscape and approaches to meet these challenges will be reviewed.